Reforma necesaria de la ley de minería a fin de regular la explotación de los materiales áridos, por parte de los gobiernos autónomos descentralizados municipales para evitar la contaminación ambiental - Yépez Mendoza, Carlos Luis (2015)
Municipal governments in accordance with the provisions of the Constitution of the Republic , have the exclusive competence to regulate , authorize and control the exploitation of aggregates and stone products called building materials, which are in the beds of rivers , lakes, beaches sea and quarrying, the Constitution determines that the hierarchical enforcement , consider the principle of competition, in particular the ownership of the exclusive competence of the Autonomous Decentralized Governments. The Organic Law on Territorial Organization , Autonomy and Decentralization , establishes exclusive jurisdiction of the Autonomous Government decentralized Municipal among other " regulate, authorize and control the exploitation of aggregates and stone materials " shall mean materials of construction rocks and their derivatives , are these sedimentary or morphological fiery nature such as , andesites , basalts, dasitas , rhyolite , granite , pumice , calcareous materials , surface clay, sand of fluvial origin or gravel : deposits alluvial type , flows, and in general all materials which process not involve a different crushing and / or particle size classification or in some cases cutting and polishing treatment , including its management and other end-use and technically established by the Ministry / Sectoral industrial process. The natural or legal person performing mining activities in the territory of the Canton , be done by a function of regulatory laws, and those contained in the Municipal Ordinances under good environmental practices , seeking the restoration of the environment and mitigating potential negative effects on the environment . The anti technique aggregates and stone materials exploitation, causing the destruction of the environment and landscape , putting at risk the neighbors and causing environmental pollution , making it necessary to have a law regulating their use and allow autonomous governments decentralized Municipal technical and environmental control thereof. The Constitution of the Republic and the Organic Law on Territorial Organization , Autonomy and Decentralization COOTAD provide that any decision or municipal authority that may affect the environment must be consulted prior to, the community , which will be informed promptly and giving it wide citizen and in case of that consultation proves overwhelming opposition of the respective community , the decision to implement or not the project will be adopted by resolution duly reasoned request higher administrative surveillance.